Atypical hemolytic uremic syndrome: a case report and review of thrombotic mechanisms - George N. Zsidisin (Journal of Rare Diseases)
Abstract Using specific clinical analyses, including genetic, hemolytic, blood, and disease manifestations, leads to a unique hypothesis about our patient’s atypical hemolytic uremic syndrome pathophysiology. Notably, a novel C3 defect, in addition to a common factor B mutation, leads to doubt over current theories of alternative complement overactivation and further drives focus onto the thrombotic nature of the disease. We propose a pathology of defective platelet-leukocyte-endothelial adhesions, leading to poor leukocyte extravasation.